2014
DOI: 10.1108/oir-04-2013-0083
|View full text |Cite
|
Sign up to set email alerts
|

Elements of the management of norms and their effects on the sense of virtual community

Abstract: Purpose -The purpose of this paper is to investigate how decisions of managers and administrators of online communities on norms and rules affect the sense of virtual community (SOVC), which is an important factor of the quality of online information. Design/methodology/approach -The study followed a two-level research design based on 970 online community members, nested within 36 online communities. Data collection consisted of two stages: first a web survey of a sample of online community members was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Participation in the formation of norms can contribute to a high Sense of Virtual Community (SOVC), the feeling of belonging and valuing an online space, but conversely a high level of explicit moderation may detract from SOVC. Notably, the reinforcement of normative behavior through rewards may be more effective than through sanctions [2]. how knowledge of norms and the ability to cite them led to more successful arguments with respect to the deletion of pages [5] "This shows Wikipedia's focus on precedent and rules, and the tendency to discuss articles in terms of both values or community norms and article contributors or supporters".…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in the formation of norms can contribute to a high Sense of Virtual Community (SOVC), the feeling of belonging and valuing an online space, but conversely a high level of explicit moderation may detract from SOVC. Notably, the reinforcement of normative behavior through rewards may be more effective than through sanctions [2]. how knowledge of norms and the ability to cite them led to more successful arguments with respect to the deletion of pages [5] "This shows Wikipedia's focus on precedent and rules, and the tendency to discuss articles in terms of both values or community norms and article contributors or supporters".…”
Section: Related Workmentioning
confidence: 99%
“…Both implicit and explicit norm enactments have a valence in terms of the emotional impact on the subject or originator. There is an assumption that for a healthy community, and to encourage the participation of newcomers, negative valence actions need to be limited or mitigated [2]. This may be related also to theories connected to social dynamics within communities of practice, where a diverse mixture of beginners and "old-timers" enables long-term sustainability [6].…”
Section: A Model Of Se Norm Enactmentmentioning
confidence: 99%
“…On the basis of the theoretical and empirical evidence reported in previous studies, we identified 3 concepts that scholars emphasize to be correlated with collective empowerment (in OHCs) [19,27,30,41,48]: sense of (virtual) community , involvement in community organization, and intensity of participation (in OHCs) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies from the field of community psychology [19,45], as well as studies on online communities [30,48], attest to the importance of participation in a community’s activities for the development of collective empowerment. Involvement in community organization pertains to online community members’ inclusion in discussions about events, vision, and strategies of the online community [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…At the firm's level, a key measure of social media success is the level of consumer engagement with the brand through the community that is facilitated on the site. In extending this thinking, if the focal point for engaged consumers is belonging to the firm's social media site community, then research should focus on the consumers' sense of belonging to such communities (Petri and Petrov, 2014).…”
Section: Introductionmentioning
confidence: 99%